New directions in adult baptism: Baptism in a secular culture - Carswell, W. John (Theology, 2018)
In this article I argue that the rise of secular culture demands a new approach to baptism, especially the baptism of adult converts for whom the claims of Christianity may be entirely unfamiliar and who will in consequence need extensive preparation to make the sacrament sensible and the Christian life meaningful. Towards that end, I review work done on the subject in the Church of Scotland and commend the Roman Catholic Rites of Christian Initiation of Adults (RCIA) as a model for the development of a full catechumenate.